Gambaran Self-Esteem saat Mengerjakan Skripsi pada Mahasiswa Universitas Bhayangkara Jakarta Raya - Leonardo Sibarani; Budi Sarasati; Timorora Sandha Perdhana (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
This study aims to describe the self-esteem levels of students at Universitas Bhayangkara Jakarta Raya in facing their thesis. Self-esteem is an individual's evaluation of themselves, both positively and negatively, influencing how they tackle academic challenges, including thesis writing. This research employs a descriptive quantitative approach using a survey method, where data were collected through questionnaires distributed to students currently working on their theses. The findings indicate that most students have a moderate level of self-esteem, with a minority categorized as having high or low self-esteem. No significant differences in self-esteem levels were found based on gender. Factors such as social support from peers and academic advisors play a crucial role in enhancing students’ self-esteem during the thesis process. This research provides insights into the importance of self-esteem in academic success and its implications for developing academic support programs in higher education institutions.